To find the sum of two numbers, we must add them together. However, in this case we are adding a negative number. Addition of a negative number can also be written as subtraction, and this method is easier for most people to compute and understand, so we are going to rewrite the expression as follows:
3 - 6
Next, we must just perform the subtraction.
3 - 6 = -3
Therefore, your answer is -3.
Hope this helps!
Answer:
a = 1 and b = - 10
Step-by-step explanation:
Expand the right side of the identity
x(ax² - 3x + b) - 3(ax² - 3x + b)
= ax³ - 3x² + bx - 3ax² + 9x - 3b
= ax³ - x²(3 + 3a) + x(b + 9) - 3b
Equate the coefficients of like terms on both sides of the identity
x³ terms → ax³ with x³ ⇒ a = 1
x terms → - x with (b + 9)x ⇒ b + 9 = - 1 ⇒ b = - 10
ANSWER
To graph the function
we need to plot some few points within one period. Since the interval is not given, we shall use
'
.
We plot the above points to obtain the graph as shown in the attachment.
Let h be height of building
then In ΔABC
AB/BC =tan60degree
h/100 = root 3
h= 100 root 3
PLEASE MARK BRAINLIST!!